"Intimacy Is the Name of the Game": Media and the Praxis of Sexual Knowledge in Nairobi - Spronk, Rachel (Anthropologica, 2022)
In the 1990s, new debates about sexuality emerged in the Kenyan media. These debates are embedded in a larger framework of personal aspirations and social transformations regarding gender, sexuality and culture that are characteristic of postcolonial Kenya. One group that embodies these trans- formations in a particular way is young middle-class adults in Nairobi. The focus of this article is on the presentation of sex- uality and intimacy in print media, on the way people appro- priate this knowledge, and how this interaction dovetails with the way sexuality has become symbolic of being a contemporary, or modern, person. The convergence between media and middle- class formation shows how modern subjectivities are created, embodied and naturalized.